2005
DOI: 10.1203/01.pdr.0000150725.78971.30
|View full text |Cite
|
Sign up to set email alerts
|

Complement C5a Is a Key Mediator of Meconium-Induced Neutrophil Activation

Abstract: Meconium aspiration syndrome is a serious condition of the newborn characterized by pulmonary inflammation with substantial neutrophil infiltration. We recently showed that meconium is a potent activator of complement. The aim of the present study was to investigate a possible role for complement in meconiuminduced neutrophil activation. Meconium was incubated in human whole blood anticoagulated with lepirudin, a specific thrombin inhibitor that does not affect complement activation. Complement activation was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 53 publications
2
17
0
2
Order By: Relevance
“…C5a is placed at the top of the list of potentially harmful inflammatory mediators. Previous studies from our group demonstrated that meconium activates neutrophils through C5a in vitro [24]. We later documented that meconium has a potential to activate the initial complement pathways on a broader basis [18].…”
Section: Inflammation In Mas - Lessons Learned From Experimental Studiesmentioning
confidence: 99%
“…C5a is placed at the top of the list of potentially harmful inflammatory mediators. Previous studies from our group demonstrated that meconium activates neutrophils through C5a in vitro [24]. We later documented that meconium has a potential to activate the initial complement pathways on a broader basis [18].…”
Section: Inflammation In Mas - Lessons Learned From Experimental Studiesmentioning
confidence: 99%
“…The role of complement activation has been shown to play an important part in the pathogenesis of acute inflammatory conditions like I/R-injury (91), meconium aspiration syndrome (MAS) (92), trauma (93) and sepsis (94). In addition complement is involved in chronic inflammatory diseases like glomerulonephritis and rheumatoid arthritis (95)(96)(97).…”
Section: Complement and Inflammationmentioning
confidence: 99%
“…Interestingly, infections and pregnancy may also induce activation of the complement system. Soluble complement activation related mediators, including anaphylatoxins and the terminal complement complex SC5b-9, may directly activate endothelial cells [11,12], neutrophils [13,14] and platelets [15,16]. Indeed, plasma of TTP patients was shown to induce apoptosis of endothelial cells and platelets [17][18][19][20] and activation of neutrophils and monocytes [21], leading to the formation of platelet-leukocyte Table 3 Correlation between complement activation product concentrations in the samples of patients with acute TTP, before the initiation of PEX-series (n = 13) complexes [22].…”
Section: Discussionmentioning
confidence: 99%